Perancangan Sistem Validasi Label Kemasan dengan Metode System Development Life Cycle (SDLC) - Mulyadi Mulyadi (Journal of Green Engineering for Sustainability, 2024)
The research conducted at PT X focuses on designing a label validation system to address customer complaints arising from discrepancies in labeling. The analytical approach employed is descriptive quantitative, utilizing the Measurement system Analysis (MSA) method. To assess the system’s effectiveness, the P control chart is used as a reliability test tool. The design of the label validation system follows the System Development Life Cycle (SDLC) methodology, specifically employing the Waterfall approach. The research outcomes demonstrate that implementing the label validation system within the company effectively reduces customer complaints. Furthermore, the system successfully minimizes discrepancies between the labels on finished goods boxes and those on attached components, eventually reaching a point of zero discrepancies.